Comprehensive Review of Moebius Syndrome: Clinical Landscape, Etiology, and Therapeutic Challenges - Navaneeth Gopal (International Journal of Bioinformatics and Computational Biology, 2024)
Moebius syndrome, a rare congenital neuromuscular disorder, presents with non-progressive facial weakness, limited eye abduction, and diverse manifestations affecting cranial nerves. This comprehensive review explores its clinical landscape, emphasizing the need for extensive investigations into its elusive etiology and genetic underpinnings. The estimated prevalence is 1 in 250,000 live births, with sporadic cases prevailing. Initial symptoms, evident from birth, encompass difficulties in sucking, and feeding, and absent facial expressiveness. Beyond musculocutaneous symptoms, diverse clinical manifestations extend to cardiac and psychiatric complications. Current research gaps, limited literature, and the absence of specific biological markers pose challenges in obtaining larger sample sizes for a more thorough understanding of the condition. The syndrome's impact on developmental milestones, cognitive function, and potential lifelong cognitive impairment necessitates a multidisciplinary approach. Surgical interventions, such as smile surgery and facial reanimation, offer corrective measures but face challenges in addressing severe congenital deformities. Lagophthalmos management, crucial for preventing complications, includes novel approaches utilizing the deep temporal nerve. Insights from ongoing genetic studies, a cross-sectional investigation into the syndrome's natural history, and an exploration of language compromise contribute to advancing our knowledge. The paper underscores the urgency for continued research to develop standardized guidelines for diagnosis and management, addressing the existing gaps in understanding this complex syndrome. The current body of literature on Moebius syndrome is limited, and existing research highlights the imperative for more extensive investigations to unravel its elusive etiology, genetic underpinnings, and optimal management strategies. The absence of specific biological markers and the rarity of the condition contribute to challenges in obtaining larger sample sizes for research.
Keywords: Computational methods; MRI; Modeling molecular interactions; Moebius Syndrome; Neuromuscular disorder; data analysis